2019
DOI: 10.1039/c8fo02163e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic supplementation on the regulation of blood lipid levels in overweight or obese subjects: a meta-analysis

Abstract: Obesity is a risk factor for many deadly diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Dyslipidemia increases the global disease burden, and elevated plasma LDL-C levels are the main risk factors for cardiovascular and cerebrovascular diseases [28]. Supplementing probiotics can improve the lipid metabolism of obese or overweight people, and can significantly reduce TC and LDL levels especially [29]. The mechanisms of probiotics regulating lipid metabolism mainly include reducing the absorption of lipids in organisms, reducing fat intake, and inhibiting the activity of key enzymes in fatty acid synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia increases the global disease burden, and elevated plasma LDL-C levels are the main risk factors for cardiovascular and cerebrovascular diseases [28]. Supplementing probiotics can improve the lipid metabolism of obese or overweight people, and can significantly reduce TC and LDL levels especially [29]. The mechanisms of probiotics regulating lipid metabolism mainly include reducing the absorption of lipids in organisms, reducing fat intake, and inhibiting the activity of key enzymes in fatty acid synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are one group of dietary ingredients or food supplements that are widely used to modify the gut microbiota. In several recent meta-analyses including subjects with mild to moderate hypercholesterolemia, these agents have been demonstrated to improve lipid metabolism, particularly to lower the total and LDL-cholesterol [64][65][66][67]. Another group of nutraceuticals that has been of interest with regard to cardiovascular health is fish oil.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Another meta-analysis also observed a slightly greater effect on SBP in hypertensive participants compared with normotensive ones [41]. Considering studies evaluating the effects of probiotics on lipid profile, recent meta-analyses revealed a statistically greater reduction in TC and LDL-col in trials with longer duration (>8 weeks) [31,67], using multiple probiotics strains [31,68], conducted in individuals with higher baseline TC [67,69] and presenting overweight or obesity [68].…”
Section: Discussionmentioning
confidence: 97%